Spontaneous chiral symmetry breaking in liquid crystals - Kats, E.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
Motivated by new experimental observations we generalize the Landau-like approach to include the direct phase transition between isotropic liquid (I) and heliconical nematic liquid crystal (NTB) structure. We show that depending on the Landau expansion coefficients, our model allows either direct I–NTB transition, or the sequence of the phases I–N–NTB with the classical nematic liquid crystal (N) sandwiched between the isotropic liquid and heliconical nematic liquid crystal. Which of these two situations is realized depends on how strong is the first order phase transition from the isotropic liquid. If it is strong enough the system undergoes I–N–NTB sequence, and for the very weak first order phase transition I–NTB transformation occurs. Furthermore in the latter case the NTB structure can be biaxial heliconical nematic liquid crystal.